Complete guide to sport education - Siedentop, Daryl; Hastie, Peter A. 1959-; Van der Mars, Hans 1955- (Human Kinetics, 2020)
"This is a textbook for undergraduate students and professional in the physical education field. It gives readers the complete guide on how to do Sport Education, a physical education instructional model. The book describes the model and why it is beneficial to students. It takes teachers through the steps of designing and implementing the model. And it concludes with content on how to integrate the model within a teacher's daily responsibilities"